1988
DOI: 10.1007/bf00027762
|View full text |Cite
|
Sign up to set email alerts
|

First year field growth of chemically root pruned containerized seedlings

Abstract: Application. Coating the interior walls of seedling containers with cupric carbonate produces seedlings of three western conifer species with more lateral roots in the upper portion of the root plug one season after outplanting. These seedlings develop a more natural root system which may improve seedling stability and growth.Abstract. Containers deform seedling root systems and have a potential to inhibit tree growth after outplanting. Ponderosa pine (Pinus ponderosa Dougl. ex Laws. var. ponderosa), western w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 3 publications
0
17
0
4
Order By: Relevance
“…var. ponderosa, o tratamento com carbonato de cobre (contendo 12% de cobre) não afetou o desenvolvimento inicial das árvores, mas ocasionou leve aumento na sobrevivência das plantas (WENNY et al, 1988).…”
Section: Introductionunclassified
“…var. ponderosa, o tratamento com carbonato de cobre (contendo 12% de cobre) não afetou o desenvolvimento inicial das árvores, mas ocasionou leve aumento na sobrevivência das plantas (WENNY et al, 1988).…”
Section: Introductionunclassified
“…En la evaluación de los tratamientos de cobre, hemos observado una tendencia a la formación de gran cantidad de raíces laterales en la parte superior del sistema radical en los tratamientos con aplicación de cobre, desarrollando así un sistema radical más similar al natural. Esto debería favorecer la estabilidad de la planta de acuerdo con lo descrito por otros autores (Burdett et al, 1983;Burdett, 1978;Wenny et al, 1988), ya que la estabilidad de un árbol parece estar condicionada por el tipo de simetría de sus raíces (Coutts et al, 1999), así como por el desarrollo excéntrico de las raíces superficiales, particularmente en zonas de mucho viento (Nicoll y Ray, 1996). Aunque la presencia o ausencia de un gran número de raíces de elevada calidad en la parte superior del taco no parece ser suficiente para presentar diferencias significativas sobre la fuerza de estabilidad, parece claro que la distribución de raíces laterales y las pivotantes sí afecta de forma dependiente a la fuerza de estabilidad.…”
Section: Biomasaunclassified
“…Once planted, root egress occurs mostly from a portion of the coalesced roots at the bottom of the plug often in one or two directions (Wenny et al, 1988;Heineman, 1991;Balisky and Burton, 1997;Krasowski and Owens, 2000). Van Eerden (1978) observed that the restriction of lateral root development was higher in lodgepole pine than hybrid spruce or Douglas fir, and that trajectory of its root egress was in the direction of their initial orientation.…”
Section: Achieving a Quality Planted Seedlingmentioning
confidence: 99%
“…Often measured in the short term, the implications of root pruning are hard to evaluate. Evidence from Burdette et al (1983), Wenny et al, (1988), Krasowski (2003), Krasowski and Owens (2000), Jones et al (2002) andRune (2003) suggest that root pruning increases root development in the upper portions of the rooted plug but the effect of root pruning is not conclusive with respect to height growth or survival. Burdette et al (1983) reported that when an applied chemical paint was added to the wall of the lodgepole pine container as compared with the non-pruned control, height growth increased in the 4-year measurements.…”
Section: Root Pruning As An Alternativementioning
confidence: 99%
See 1 more Smart Citation